Studi Eksperimental: Hubungan Media Pendinginan Dengan Kekerasan Dan Struktur Mikro Aluminium Bekas Profil Dengan Metode Lost Foam Casting - Bambang Tjiroso (Journal of Science and Engineering, 2026)
AbstractThis study aims to explore the relationship between the cooling medium and the hardness and microstructure of used aluminum profiles processed using the Lost Foam Casting (LFC) method. Results Hardness testing using the Rockwell A method was conducted, yielding hardness values of 19.08 HRA for water cooling, 20.03 HRA for oil cooling, and 19.03 HRA for air cooling. Rapid cooling media such as water or oil generally increase material hardness compared to air cooling; however, the specific order and magnitude of the differences may vary depending on material properties and the heat treatment parameters used. These hardness differences are related to microstructure: media with higher cooling rates (water and especially oil) tend to produce finer α-Al grains and a better distribution of the Al–Si phase, whereas air cooling allows for larger grains and higher porosity, resulting in slightly lower hardness.